ИССЛЕДОВАНИЕ ОБРАЗОВАНИЕ Δ0-ИЗОБАР В ЦЕНТРАЛЬНЫХ p12C- И d12C-СОУДАРЕНИЯХ ПРИ 4.2 A ГэВ/с - Бекмирзаев, Р.; Олимов, К.; Юлдашев, Б.; Султанов, М.; Юлдашев, С. (SCIENCE and SOCIETY, 2025)
The present paper presents experimental data on various characteristics of Δ0-isobars formed in central p12C- and d12C- collisions at 4.2 A GeV/c. Take the number of participating protons formed in these events as the degree of centrality. Experimental values of the average multiplicity of participant protons are determined for the studied collisions. It is shown that in both types of collisions the value of the effective mass and the width of the mass spectrum of these isobars were found to coincide with each other.
Keywords: nucleus; nucleon; Δ-isobar; effective mass; mass spectrum width; charged particles; central collision; accelerator; propane chamber; carbon